Patterns in weight and physical activity tracking data preceding a stop in weight monitoring: Observational analysis - Frie, K; Hartmann-Boyce, J; Jebb, S; Oke, J; Aveyard, P (JMIR Publications Inc., 2020)
Background: Self-regulation for weight loss requires regular self-monitoring of weight, but the frequency of weight tracking commonly declines over time.